TINJAUAN MANFAAT BUNGA TELANG (CLITORIA TERNATEA L.) BAGI KESEHATAN MANUSIA - Marpaung, Abdullah Muzi (Swiss German University & Perhimpunan Penggiat Pangan Fungsional dan Nutrasetikal Indonesia (P3FNI), 2020)
All part of the butterfly pea (Clitoria ternatea) plant reported having a various positive effect on human health. The blue petal, in particular, shows a wide range of functional activity including as an antioxidant, antidiabetic, antiobesity, anticancer, anti-inflammatory, and antibiotic. The hydrophilic phase of butterfly pea flower extract contains flavonol glycosides, anthocyanins, flavones, flavonols, phenolic acids, and cyclotides. Meanwhile, the terpenoids, alkaloids, and fatty acids were found in the lipophilic phase of butterfly pea flower extract. The proven health benefits and the wide range of the type of bioactive compounds promote butterfly pea flower as the source of functional food and nutraceuticals. However, a series of intensive research, including the clinical trial, is still needed.